Perancangan Sistem Informasi Perhitungan Angka Kredit Kenaikan Jataban Fungsional Dosen - Kristiawan Kristiawan; Chairullah Naury; Mursid Dwi Hastomo (Indonesian Journal of Information Technology and Computing (IMAGING), 2025)
Promotions are given to increase the work motivation of lecturers so they can carry out their duties to the fullest. The main elements as a position assessment are education, research, community service and supporting elements for the main duties of lecturers. The problem faced by the lecturers at Sebelas Maret University Surakarta (UNS) was a lack of time in preparing the documents for promotion due to the large amount of credit score data that had to be compiled manually. For this reason, it is necessary to build an information system that makes it easier for lecturers to compile proposals for promotion and find out the actual achievement of credit scores. Based on the description of the problem above, the formulation of the problem to be solved in this study is, "How to design an information system for calculating credit score increases in the functional composition of lecturers at the Faculty of Law, UNS". This study uses the System Development Life Cycle (SDLC) method with the Waterfall model with the object under study is a lecturer credit score calculation system based on the attachment to Minister of Education and Culture No.92 of 2014 to build an information system for calculating credit score for lecturer promotion. The programming language used to design this information system is PHP Native with MySQL database for data storage.